MONITORING OF SURFACE WATER RESOURCE DYNAMICS IN A SEMI-ARID ENVIRONMENT OF NIGERIA: A DIGITAL CHANGE DETECTION APPROACH - Yaro, A.; Adamu, G. K.; Muhammed, I. (FUDMA Journal of Sciences, 2023)
The aim of this paper is to monitor surface area change of Zobe dam water body in central part of Katsina State. The methods adopted to detect changes include Land use/land cover change assessment in relation to the water body in Zobe dam watershed using satellite image processing, change detection of multi-temporal images and supervised classification using Maximum Likelihood algorithm in ERDAS imagine 2014. This was achieved using multispectral Landsat 7 satellite data of the year 2005 and Landsat 8 OLI of the year 2015 respectively. The study area was classified into five major classes viz: Built up areas, Waterbodies, Bare surfaces, Plantation and Farmlands. Post classification Change detection analysis was performed to compare the quantities of land cover class conversions over spatial and temporal scales. Results revealed that surface dimension of the water body of Zobe dam decreased from 270.48km2 to 259.40km2 between 2005 and 2015 respectively. This amounted to a decrease of 11.08km2within a ten-year period with an annual rate of decrease of 1.1km2. Plantation also decreased from 160.19km2 in 2005 to 92.34km2 implying a loss of 67.85km2within a period of only ten years. It further revealed increase in bare surface, builtup areas and farmlands from 2005 to 2015. Drivers of the observed changes includes rapid population growth leading to establishment and expansion of existing and new settlements which resulted into widespread conversion of natural vegetated cover to large expanse of cultivated land with serious consequences on the environment. Thus, a detailed and regular study of condition.
Keywords: Image Classification; Zobe Dam; Water Resources; Change Detection; Semi-arid; Land Cover; Land Use